Pengembangan Sistem Keamanan Kendaraan Bermotor Menggunakan Teknologi Fingerprint dengan Metode Prototype Berbasis Internet Of Things - Somantri Somantri; Gina Purnama Insany; Roby Ryansyah (Universitas Islam Raden Rahmat, Malang, 2024)
With the increasing number of motor vehicles, the demand for sophisticatedsecurity systems has become more imperative. This research focuses on thedevelopment of a motor vehicle security system utilizing fingerprint technologywith an Internet of Things (IoT)-based approach.The system is powered by theNodeMCU ESP32, enabling access through fingerprint verification to replacethe use of physical keys or remote controls, as well as conventional motor contactand starter mechanisms. The GPS module provides advanced trackingcapabilities, allowing real-time monitoring of the vehicle's position through anAndroid application. Firebase functions as the real-time database for thestorage and management of user data and the location of the vehicle. Throughthe implementation of the Internet of Things, vehicle owners can access andcontrol the security of their vehicles in real-time using smart devices such assmartphones. This development method is tested to measure the level of securityand user convenience. The research outcomes are anticipated to make a positivecontribution to the advancement of motor vehicle security systems, aiming toreduce vehicle theft and provide an effective and practical solution for ensuringvehicle security.